Faktor-Faktor Yang Mempengaruhi Profitabilitas Pada Perusahaan Sektor Usaha Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Wellin Andrea; Fanky Dewi Lie Gunardy; Michelle Aurelia Yapinka; Alfan Wijaya; Bayu Wulandari; Muhammad Habibie (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Business profit is the main goal of establishing a company by a group of individuals who run their business. Every year, the owner will set a profit target to be achieved so that management as directors try to optimize all assets owned by the company, both short-term and long-term assets. To achieve profit goals from business activities, the company will try to maintain short-term ratio stability, fast payments, inventory turnover, receivables turnover, DER system and working capital turnover so that every year the company operates well and stably and is relatively stable in the business as it runs. The aim of this research is to analyze the effect of the current ratio, quick ratio, inventory turnover, accounts receivable turnover, DER and partial working capital turnover as well as on the profitability of consumer goods industrial companies listed on the IDX. The basic group includes no less than 73 companies in the consumer goods industry, the sampling method is purposive sampling so that sample includes 37 companies and no less than 111 observations were made. Data analysis techniques are multiple linear regression, classical assumption testing and hypothesis testing. The research results show that the current ratio, debt ratio, inventory turnover, accounts receivable turnover, and DER ratio partially have a positive and significant effect on the profitability (ROA) of consumer goods companies listed on the IDX, while working capital circulation has no significant effect on the company’s profitability. Meanwhile, the current ratio, quick ratio, inventory turnover, receivables turnover, DER ratio and working capital turnover have a significant effect on the ROA of consumer goods companies on the IDX.There is a strong correlation between a company’s current metrics, short-term metrics, inventory turnover, receivables turnover, DER, working capital turnover and ROA. ROA can be explained by the Current ratio, Quick Ratio, Inventory Turnover, Receivables Turnover, DER and Working Capital Turnover. 55,5% the remaining 44.5% can be explained by other variables that have not been tested. Keywords: Current ratio, Quick Ratio, Inventory Turnover, Receivables Turnover, DER, Working Capital Turnover, ROA